Price movement in the Brazilian land market (1994-2010): an analysis in the light of post-Keynesian theory - Santos Telles, Tiago; Antonio Palludeto, Alex Willhans; Philip Reydon, Bastiaan (Brazilian Journal of Political Economy, 2016)
The present study aims to evaluate crop, pasture and forest land prices in Brazil, between 1994 and 2010, in the light of Post Keynesian theory. The results provide evidence that land, more than just a simple factor of production, must be conceived of as an economic asset. In fact, the price of rural land is determined not only by the expected profitability deriving from agricultural activities but also by the agents’ expectations about its future appreciation and liquidity in an economic environment permeated with uncertainty. In this context, as an object of speculation, land has been particularly important as a store of value. JEL Classification: E12; G11.